1999
DOI: 10.1080/026811199282100
|View full text |Cite
|
Sign up to set email alerts
|

Codes for spread spectrum applications generated using chaotic dynamical systems

Abstract: An approach to finding codes for use in direct sequence spread spectrum communications systems is described. It is based upon an analogy between codes having auto-and cross-correlation properties desirable for spread spectrum systems, and certain dynamical systems encountered in ergodic theory called systems with Lebesgue spectrum. Such systems are associated with collections of orthogonal functions and these functions can be used to generate collections of time series with zero cross-correlation functions. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In both cases, the sequences from chaotic maps were quantized and truncated so that the sequences were actually periodic. Broomhead et al have shown another method of generating spreadspectrum sequences from UPO's [26].…”
Section: General Approachmentioning
confidence: 98%
“…In both cases, the sequences from chaotic maps were quantized and truncated so that the sequences were actually periodic. Broomhead et al have shown another method of generating spreadspectrum sequences from UPO's [26].…”
Section: General Approachmentioning
confidence: 98%
“…This map is able to produce a variety of distinct sequences for different users, by just changing the initial states and/or its bifurcation parameter. The proposed algorithm in [12] uses locally-generated chaotic codes to spread transmitted signals on the available bandwidth, which guarantees secure protection against eavesdropping (as packets can only be decoded with the 6 proper chaotic code, which depends on the secret initial conditions/seed), transmitter-receiver self-synchronization, and good auto-and cross-correlation properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, stable or unstable periodic orbits of arbitrary length in a given chaotic system can be determined to any desired accuracy, so that a tailored set of such periodic sequences can be very useful [7][8][9][10]. In using UPO binary sequences for digital communication, it is necessary to find suitable control parameters for the selected chaotic system in order to optimize the digital machines generating the codes.…”
Section: Introductionmentioning
confidence: 99%